Necessary existence and monotheism an Avicennian account of the Islamic conception of divine unity - Zarepour, Mohammad Saleh ca. 20./21. Jh (Cambridge University Press, 2022)
Avicenna believes that God must be understood in the first place as the Necessary Existent (wâǧib al-wuǧûd). In his various works, he provides different versions of an ingenious argument for the existence of the Necessary Existent-the so-called Proof of the Sincere (burhân al-ṣiddîqîn)-and argues that all the properties that are usually attributed to God can be extracted merely from God's having necessary existence. Considering the centrality of tawḥîd to Islam, the first thing Avicenna tries to extract from God's necessary existence is God's oneness. The aim of the present Element is to provide a detailed discussion of Avicenna's arguments for the existence and unity of God. Through this project, the author hopes to clarify how, for Avicenna, the Islamic concept of monotheism is intertwined with the concept of essential existence
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: Avicenna / 980-1037; God (Islam) / Proof / History of doctrines